Europe and MENA cooperation advances in information and communication technologies - Rocha, Álvaro; Serrhini, Mohammed; Felgueiras, Carlos (Springer, 2016)
This book contains a selection of articles from The Europe, Middle East and North Africa Conference on Technology and Security to Support Learning 2016 (EMENA-TSSL'16), held between the 3th and 5th of October at Saidia, Oujda, Morocco. EMENA-TSSL'16 is a global forum for researchers and practitioners to present and discuss recent results and innovations, current trends, professional experiences and challenges in Information & Communication Technologies, and Security to support Learning. The main topics covered are: A) Online Education; B) Emerging Technologies in Education; C) Artificial Intelligence in Education; D) Gamification and Serious games; E) Network & Web Technologies Applications; F) Online experimentation and Virtual Laboratories; G) Multimedia Systems and Applications; H) Security and Privacy; I) Multimedia, Computer Vision and Image Processing; J) Cloud, Big Data Analytics and Applications; K) Human-Computer Interaction; L) Software Systems, Architectures, Applications and Tools; M) Online Languages and Natural Language Processing N) E-content Development, Assessment and Plagiarism; O) Secure E-Learning Development and Auditing; P) Internet of Things and Wireless Sensor Networks.
Keywords: Information technology -- Congresses.; Artificial intelligence -- Congresses.; Cloud computing -- Congresses.; elektronické knihy; electronic books